NIANTIC LIGHTSHIP BASED AUGMENTED REALITY FOR ENHANCING IPAS LEARNING IN ELEMENTARY EDUCATION - Ria Andriani; Muhammad Jaelani Ramadhan Ash Shidiq (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2026)
Abstract concepts in Natural and Social Sciences (IPAS), particularly the complete metamorphosis of butterflies, often present visualization challenges for elementary school students. This study addresses this issue by developing an interactive markerless Augmented Reality (AR) application using Niantic Lightship ARDK. The application employs Meshing and Occlusion features to enhance spatial immersion. Following the Multimedia Development Life Cycle (MDLC) method, a one-shot case study design (N=22) was used to evaluate the software’s functional feasibility and the students’ basic cognitive mastery. Functional testing across various mid-range Android devices indicated technical stability, confirming that advanced AR features can operate on standard hardware. Expert validation rated the media as “Highly Feasible” with a maximum score. Preliminary testing on student learning outcomes yielded an average post-test score of 94.09% with a 90.9% classical mastery level. Although limited by a small sample size and the absence of a control group, these findings suggest that the developed AR application is functional and contributes to student comprehension in IPAS learning.